Dermatophytes isolated from dogs and cats suspected of dermatophytosis in Southern Brazil - Copetti, Marina Venturini; Santurio, Janio Morais; Cavalheiro, Ayrton Sydnei; Boeck, Ana Aurea; Argenta, Juliana Siqueira; Aguiar, Leila Canabarro; Alves, Sydnei Hartz (Acta Scientiae Veterinariae, 2018)
Dermatophytosis which is characterized by a superficial infection confined to keratinised tissues, is the most common fungal disease in small animal veterinary medicine. It is unreliable to diagnose dermatophytosis on the basis of clinical signs alone, not only for the variable nature of the dermatological findings but also because there are several other skin diseases which mimic the typical fungal lesion (circular lesions with alopecia). The present study reports laboratory results of an extensive survey evaluating fungal and parasitic aetiology of skin diseases through the analysis of 1,240 fur, nails and skin scraping specimens from dogs and cats with clinical suspicion of dermatophytosis. Samples collected in several veterinary clinics of the Santa Catarina, Paraná and Rio Grande d o Sul states, mainly of the Santa Maria city in Rio Grande do Sul, were processed at the Mycology Research Laboratory of the Federal University of Santa Maria, Southern Brazil, between 1998 and 2003. Among canine and feline samples, the percentages of positive dermatophyte specimens were 10.2% and 27.8%, respectively. The most prevalent fungal specie in both cats and dogs was Microsporum canis, which was isolated in 68.5% of the positive cultures for dermatophytes in dogs’ samples, being the only species recovered from cats’ cultures. Malassezia pachydermatis was the most commonly isolated yeast from the skin of dogs. Acari, mainly Demodex canis, were found in 5.0% of all samples with suspected diagnosis of dermatophytosis.